Angels and Devils in the Traditional Lithuanian Worldview: Affinities and Oppositions - Šlapikienė, Solveiga (Tautosakos darbai, 2024)
In the article, I examine the allegedly opposing supernatural beings of the traditional Lithuanian worldview – angels and devils. Primarily, I discuss the ways of depicting the relationship between angels and devils in the Lithuanian folk narratives. The article aims at establishing features of angels and devils revealed in folklore, when both of them perform their activities under similar circumstances. It focuses on mythical common origins of the angels and devils and their activities as human companions.According to my study, the affinity of the angels and devils is based, first, on their common primeval angelic nature, and on the functions that they perform, including their proximity to humans: following them in the course of their entire life and transporting their souls to another world after death. However, the actions of angels and devils respectively have different motivation, since they obey opposing forces that govern the world, namely, God or Lucifer. In folk narratives, activities of angels and devils are largely related to humans, and the human soul is their main goal; this reflects the important side of the traditional Lithuanian worldview – a constant battle between forces divine and demonic.
Keywords: angels; devils; Lithuanian folklore; traditional worldview; Christian mythology